2019
DOI: 10.1371/journal.pone.0216391
|View full text |Cite
|
Sign up to set email alerts
|

A chronic kidney disease patient awareness questionnaire: Development and validation

Abstract: Background With the advance of medical care, chronic non-communicable diseases, like chronic kidney disease (CKD), have become the predominant diseases around the world. With heavy society and economy burden, we shall make full use of chronic disease management, including precision therapies. And the prerequisite for implementing precision medicine is to fully understand the characteristics of patients. Being the basis of the Knowledge-Attitude-Practice Model, patient’s awareness is essential to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…This was the first study conducted on CKD awareness in AJ&K. Results showed satisfactory awareness of about 56% (42.3 is the average awareness score out of 72). Past studies on CKD patients showed low awareness 23 to 40% in nonhemodialysis patients in Africans-American patients, [16,17] 45.6 % awareness in Kenya, [18] 29 % awareness in Africa, [16] satisfactory awareness in China, [19] poor awareness in Australia, [20] poor awareness in Nigeria. [21] Cronbach's alpha showed that the questionnaire has acceptable reliability, a = 0.82 near to original study of validation by Peng S et al in 2019 in China (a = 0.852) (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the first study conducted on CKD awareness in AJ&K. Results showed satisfactory awareness of about 56% (42.3 is the average awareness score out of 72). Past studies on CKD patients showed low awareness 23 to 40% in nonhemodialysis patients in Africans-American patients, [16,17] 45.6 % awareness in Kenya, [18] 29 % awareness in Africa, [16] satisfactory awareness in China, [19] poor awareness in Australia, [20] poor awareness in Nigeria. [21] Cronbach's alpha showed that the questionnaire has acceptable reliability, a = 0.82 near to original study of validation by Peng S et al in 2019 in China (a = 0.852) (19).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies on CKD patients showed low awareness 23 to 40% in nonhemodialysis patients in Africans-American patients, [16,17] 45.6 % awareness in Kenya, [18] 29 % awareness in Africa, [16] satisfactory awareness in China, [19] poor awareness in Australia, [20] poor awareness in Nigeria. [21] Cronbach's alpha showed that the questionnaire has acceptable reliability, a = 0.82 near to original study of validation by Peng S et al in 2019 in China (a = 0.852) (19). P Gheewala et al study in Australia showed a = 0.88 (20), Li Lou et al e-version study in China showed a = 0.962 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Patients-reported outcomes (PROMs) will be used to identify lifestyle factors, selfefficacy, psychological status and quality of life. A cognitive questionnaire will be given to determine patients' cognitive levels so that the nursing group can schedule receptive and individualized courses [37]. Social support score will be collected by the Social Support Rating Scale (SSRS), self-efficacy score will be assessed by General Self-Efficacy Scale (GSES), and patient and doctor relationship will be measured by a developed Patient-Doctor Relationship Questionnaire (PDRQ-13) [38][39][40].…”
Section: Exposure Measuresmentioning
confidence: 99%
“…8,9 Existing measures tend to be nonspecific, evaluating chronic disease broadly, or include questions relating to symptoms and therapies that are common only in later-stage CKD, such as dialysis-related fatigue, fistula management, and monitoring blood phosphorus levels. [10][11][12][13][14][15][16][17][18] We identified 3 existing questionnaires that were relevant to CKD self-management for patients not on KRT. 14,15,19 These questionnaires served as excellent references for item identification for the first iteration of our CKD-SM questionnaire.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Moreover, clinicians and content experts developed many of these existing questionnaires with little, or no, input from patients and caregivers, and so the questionnaires may not reflect patients' self-management needs and priorities. Four related questionnaires, developed to address CKD awareness and/or self-management, 14,15,19,20 have been used to assess self-management in CKD. However, these questionnaires were developed and validated in China and Taiwan, which introduces some cultural context and translation challenges that may limit "conceptual equivalence" of the questionnaires in a Canadian context.…”
Section: Introductionmentioning
confidence: 99%